2022
DOI: 10.1186/s13578-022-00870-y
|View full text |Cite
|
Sign up to set email alerts
|

Current methodologies in protein ubiquitination characterization: from ubiquitinated protein to ubiquitin chain architecture

Abstract: Ubiquitination is a versatile post-translational modification (PTM), which regulates diverse fundamental features of protein substrates, including stability, activity, and localization. Unsurprisingly, dysregulation of the complex interaction between ubiquitination and deubiquitination leads to many pathologies, such as cancer and neurodegenerative diseases. The versatility of ubiquitination is a result of the complexity of ubiquitin (Ub) conjugates, ranging from a single Ub monomer to Ub polymers with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 107 publications
1
18
0
Order By: Relevance
“…Chain position, linkage type, and topology determine the fate of a ubiquitylated substrate. The linkage polyubiquitination leading to proteasomal degradation typically occurs on K48-linked chains. , The determination of the nature of the substrate ubiquitination is technically challenging. ,, Figure D of Sun et al showed a linkage analysis indicating that 32% was from ubiquitin K48 (no further information was provided on this analysis). It was stated that “because K48 was the most abundant linkage type, much of the chloroplast ubiquitinome can be assumed to be primed for proteasomal degradation.” However, there are two issues with this analysis: (i) we identified 5500 proteins in these samples of which only ∼25% was chloroplast-localized (Table ) and (ii) off-target lysine di-carbamidomethylation is confounding this analysis.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chain position, linkage type, and topology determine the fate of a ubiquitylated substrate. The linkage polyubiquitination leading to proteasomal degradation typically occurs on K48-linked chains. , The determination of the nature of the substrate ubiquitination is technically challenging. ,, Figure D of Sun et al showed a linkage analysis indicating that 32% was from ubiquitin K48 (no further information was provided on this analysis). It was stated that “because K48 was the most abundant linkage type, much of the chloroplast ubiquitinome can be assumed to be primed for proteasomal degradation.” However, there are two issues with this analysis: (i) we identified 5500 proteins in these samples of which only ∼25% was chloroplast-localized (Table ) and (ii) off-target lysine di-carbamidomethylation is confounding this analysis.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Based on our own analysis presented here, the most recent reviews on “ubiquitinomics”, ,,,,,, and the primary literature, we recommend the following for the MS-based determination of possible in vivo ubiquitination of intra-chloroplast proteins of viable and intact chloroplasts: Ensure that the plants are not under significant chloroplast stress (e.g., due to high light treatment) as this will result in (a) rapid release of chloroplast proteins into the cytosol as demonstrated by confocal microscopy of plants expressing chloroplast-targeted green fluorescent protein (GFP) in the flu mutant , and (b) ATG-dependent and independent autophagy of swollen or otherwise damaged chloroplasts or selected chloroplast content and delivery and degradation in the vacuole. , Use low concentration of appropriate (e.g., CAA but not IAA) alkylating agents (e.g., 20 mM) for in-solution digests and ensure removal or quenching of alkylating agent prior to addition of trypsin (or other proteases) to avoid N-terminal peptide and lysine alkylation. An alternative method to block the cysteine sulfhydryl group without the introduction of any potentially confounding acetamide at all is by treatment with S-methyl methanethiosulfonate (MMTS) with a +45.9877 modification or acrylamide resulting in a +71.037 modification .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ubiquitin system is most well-known for its role in managing protein degradation [ 1 ], however ubiquitin transfer (ubiquitylation) has extensive non-proteolytic roles including the recruitment of signalling complexes [ 2 ], and regulating the cellular localisation of proteins [ 3 ]. Proteins can be modified by single ubiquitin moieties or by polyubiquitin chains of eight different linkages [ 4 ]. Attachment of ubiquitin involves a cascade of three families of proteins.…”
Section: Introductionmentioning
confidence: 99%